Technological management of knowledge: modern tool for management of educational institutions - Niebles-Núñez, William Alejandro; Hernández-Palma, Hugo G.; Cardona-Arbeláez, Diego (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this article is to present a theoretical reflection directed to analyze technological management of knowledge as a modern tool for administration of educational organizations. It was framed as a descriptive theoretical reflection. It was used bibliographic observation through the signing as technique. Among reflections, it was found that the strategies used, although not very stable, were: use of collaborative spaces, systems of information retrieval, management, and use of experts, as well as knowledge-based systems. However, document management techniques were scarce. Finally, as recommendation, developing dynamic activities between groups of teachers is proposed, in this way, the knowledge of emotions that leads to greater optimism and motivation can be consolidated.